FTA science on wetlands helps refine Indonesian measurement, reporting and verification and forest reference emission level development - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA has played an active role in the design of Indonesia’s Forest Reference Emission Levels (FRELs) submission to the United Nations Framework Convention on Climate Change (UNFCCC) by co-producing relevant data and knowledge products, building capacity among key personnel and stakeholders, and creating a platform for communication, engagement and outreach at national and international levels.